Baseline detrusor pressure and renal reserve as determinants of botulinum toxin a response in pediatric neurogenic bladder (Annals of Medical Research, 2026)
Aim: Pediatric neurogenic bladder (NB) jeopardizes both lower and upper urinary tract integrity. This study evaluated the pressure-lowering efficacy of intradetrusor botulinum toxin A (BTX-A) in children with spinal-origin NB and identified clinical and urodynamic predictors of treatment response.Materials and Methods: In this retrospective cohort study, 38 pediatric patients with spinal-origin NB who received 100 IU of BTX-A between October 2023 and December 2024 were analyzed. BTX-A was injected cystoscopically at 20 detrusor sites, sparing the trigone. The primary outcome was the 6-month change in storage-phase detrusor pressure (Δp_det), calculated as p_det = p_ves − p_abd per ICCS standards. Secondary outcomes included an exploratory responder endpoint (≥10 cmH₂O reduction in storage pressure) and attainment of guideline-based safe storage thresholds (
Keywords: Pediatric neurogenic bladder; Botulinum toxin A; Detrusor pressure; Renal function; Spinal dysraphism